2022
DOI: 10.1111/cas.15491
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with anamorelin and a myostatin inhibitor is advantageous for cancer cachexia in a mouse model

Abstract: Cancer cachexia is a multifactorial disease that causes continuous skeletal muscle wasting. Thereby, it seems to be a key determinant of cancer‐related death. Although anamorelin, a ghrelin receptor agonist, has been approved in Japan for the treatment of cachexia, few medical treatments for cancer cachexia are currently available. Myostatin (MSTN)/growth differentiation factor 8, which belongs to the transforming growth factor‐β family, is a negative regulator of skeletal muscle mass, and inhibition of MSTN s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Myostatin decline was accompanied by inhibiting Smad2 transcription factor phosphorylation and activation [78]. TGF-β/Smad signaling was an important regulator of stress response and was associated with mood disorders' behavioral outcomes [79].…”
Section: Discussionmentioning
confidence: 99%
“…Myostatin decline was accompanied by inhibiting Smad2 transcription factor phosphorylation and activation [78]. TGF-β/Smad signaling was an important regulator of stress response and was associated with mood disorders' behavioral outcomes [79].…”
Section: Discussionmentioning
confidence: 99%
“…88 Inhibiting the myostatin signaling pathway has been subject of various (pre-)clinical trials aiming at identifying therapeutic means for conditions associated with, for example, cancer cachexia, and the myostatin propeptide and modified (minimum) amino acid sequences derived from the propeptide composition were suggested as promising drug candidates. 146 focused on testing approaches concerning myostatin inhibitory peptides with molecular masses between 1.7 and 2.9 kDa. 89 investigated the traceability and metabolic fate of insulin-mimetic peptides referred to as S597 and S519.…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%
“…Inhibiting the myostatin signaling pathway has been subject of various (pre‐)clinical trials aiming at identifying therapeutic means for conditions associated with, for example, cancer cachexia, and the myostatin propeptide and modified (minimum) amino acid sequences derived from the propeptide composition were suggested as promising drug candidates 146 . Internet‐based suppliers have offered myostatin propeptide preparations for research purposes, and means to monitor a potential misuse in sports has been required.…”
Section: β2‐agonists Hormone and Metabolic Modulatorsmentioning
confidence: 99%
“…Notably, previous research has demonstrated that mutations or absence of myostatin leads to significant muscle growth in humans and vertebrate animals [ 169 , 170 , 171 , 172 , 173 ]. Moreover, several studies have indicated that inhibition of myostatin could potentially help preserve skeletal muscle in tumor-bearing animal models [ 174 , 175 , 176 , 177 ] as well as in cancer patients [ 178 ]. A recent study demonstrated the protective effect of myostatin inhibition by attenuating soluble ActRIIB, which prevented not only skeletal muscle loss but also cancer-induced cardiac muscle atrophy [ 179 ].…”
Section: Myokines As Potential Therapeutic Agents For Cancer Cachexiamentioning
confidence: 99%